Examining lexical and grammatical diﬃculties in Bengali language using NLP with machine learning - Afroz, Sazia; Susmoy, M. Samiur Rahman; Anjum, Farhan; Nowshin, Nadiya (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.